2016
DOI: 10.18632/oncotarget.9819
|View full text |Cite
|
Sign up to set email alerts
|

MEF2C rs190982 polymorphism with late-onset Alzheimer's disease in Han Chinese: A replication study and meta-analyses

Abstract: The myocyte enhancer factor (MEF2) family of transcription factors plays a vital role in memory and learning due to its functions in regulating synapse number and reducing dendritic spines. Myocyte enhancer factor 2 C (MEF2C) is regarded as modulator of amyloid-protein precursor (APP) proteolytic processing, in which amyloid-β (Aβ) is produced. A common single nucleotide polymorphism (SNP, rs190982) in MEF2C gene was identified to be related to late-onset Alzheimer's disease (LOAD) in Caucasians in a large met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Besides the most consistent genetic risk factor ApoE for Sporadic AD, some studies have also reported many genetic risk factors that appear distinct AD susceptibility between Caucasian and East Asian populations. For instance, following genes were proven to be only associated with AD risk in Caucasian populations but not in East Asian populations: Triggering Receptor Expressed On Myeloid Cells 2 (TREM2) [44, 45], Solute Carrier Family 24 Member 4 (SLC24A4) [46], NME/NM23 Family Member 8 (NME8) [47], GRB2 Associated Binding Protein 2 (GAB2) [48], Myocyte Enhancer Factor 2C (MEF2C) [49], Inositol Polyphosphate-5-Phosphatase D (INPP5D) [50], CLU [51], ABCA7, CD2AP, and EPHA1 [25], Fermitin Family Member 2 (FERMT2) [52]. Hence, the complex difference among different ethnicities and races probably cause the genetic heterogeneity of AD between Caucasians and East Asians.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the most consistent genetic risk factor ApoE for Sporadic AD, some studies have also reported many genetic risk factors that appear distinct AD susceptibility between Caucasian and East Asian populations. For instance, following genes were proven to be only associated with AD risk in Caucasian populations but not in East Asian populations: Triggering Receptor Expressed On Myeloid Cells 2 (TREM2) [44, 45], Solute Carrier Family 24 Member 4 (SLC24A4) [46], NME/NM23 Family Member 8 (NME8) [47], GRB2 Associated Binding Protein 2 (GAB2) [48], Myocyte Enhancer Factor 2C (MEF2C) [49], Inositol Polyphosphate-5-Phosphatase D (INPP5D) [50], CLU [51], ABCA7, CD2AP, and EPHA1 [25], Fermitin Family Member 2 (FERMT2) [52]. Hence, the complex difference among different ethnicities and races probably cause the genetic heterogeneity of AD between Caucasians and East Asians.…”
Section: Discussionmentioning
confidence: 99%
“…The differential SNP associations across ethnic groups is expected based on the reported differences in the genetic architecture of human populations (Grinde et al, 2019;Sirugo et al, 2019). For example, a MEF2C SNP (rs190982) was associated with LOAD risk in Caucasians, but not in Han Chinese (Tang et al, 2016). The observation that the associated variants may have inconsistent direction of effect (positive effect in NHW and a negative effect in CH or vice versa) is not atypical and most likely attributable to population-specific linkage disequilibrium patterns.…”
Section: Discussionmentioning
confidence: 98%
“…Studies in mouse models demonstrated that MEF2C is strongly expressed in several brain areas (hippocampus, dentate gyrus, amygdala, etc.) (Rashid et al, 2014) and it may modulate the reduction of dendritic spine growth (Rashid et al, 2014;Tang et al, 2016). In mice, the deletion of MEF2C gene was linked to impairments in learning and memory (Barbosa et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from animal models also suggests that it is involved in the development of memory and the consolidation of information 34 . Over-expression of MEF2C has also been implicated in poor developmental and cognitive outcomes 36 , 37 and it has been associated with Alzheimer’s disease 38 . Given its apparently more general role in cognition, and the lower but not trivial associations with maths (p = 5.12 × 10 –6 ) and English (p = 9.76 × 10 –5 ), we are not suggesting MEF2C is a science specific gene.…”
Section: Discussionmentioning
confidence: 99%